Fostering Meaningful and Creative Connections in Higher Education: Contributions from Music Education - Milhano, Sandrina (2021)
This paper focuses on contributing to the reflection on the importance of providing opportunities to foster meaningful and creative connections in higher education. In a context of growing plurality, heterogeneity and diversity of backgrounds, languages, cultures, identities, roles, and purpose influences the sociocultural relations and professional interactions that occur and are formed within higher education communities of knowledge and learning, which are explored from the perspective of music education. A narrative approach on participant’s views about their participation in an elective music program was developed inside the framework of informal education. Issues that were discussed the most across the datasets by participants individual accounts are expressed through themes that fall into three broad areas: previous musical experiences, significant influences for music participation, and perceptions of the participation in the music program. Results suggest that the informal music program provided participants with a context for a safe emotional, social, cultural, and musical experience, and thus heterogeneity and diversity are seen as enriching factors. Some considerations are made on the ways through which music can help to foster connections and sense of humanity in higher education. This provides some insights into the relevance of fostering musical participation as part of the cultural responsibility of higher education institutions for participants.